2016
DOI: 10.1177/1070496516664385
|View full text |Cite
|
Sign up to set email alerts
|

Assessing natural resource management through integrated environmental and social-economic accounting

Abstract: Local natural resource management in its diverse manifestations holds core to its principles that the marginal and vulnerable households are empowered to manage valuable natural resources to improve social and economic equality and conserve biodiversity. Yet studies aiming to identify the impacts often show inconsistent results. Through constructing an integrated Environmental and Social Accounting Matrix (ESAM), we aim to assess how natural resources are used in different sectors and by different livelihoods,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Our study has shown that relative to Zambians in the south western corner of Zambia, Namibian conservancy members' tolerance and perceptions of intangible benefits toward some wildlife species are more positive—most likely as a result of the economic approach taken in Namibia's CBNRM program. While Namibia's CBNRM program is not perfect, (Khumalo & Yung, 2015; Koot, 2019; Lubilo & Hebinck, 2019; Morton, Winter, & Grote, 2016; Nuulimba & Taylor, 2015; Schnegg & Kiaka, 2018), relative to Zambia, Namibians in the Zambezi region seem to be better off both in terms of monetary and intangible benefits from wildlife. Our results should however be considered of an exploratory nature as we acknowledge that due to multiple testing, there is a risk of false findings.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has shown that relative to Zambians in the south western corner of Zambia, Namibian conservancy members' tolerance and perceptions of intangible benefits toward some wildlife species are more positive—most likely as a result of the economic approach taken in Namibia's CBNRM program. While Namibia's CBNRM program is not perfect, (Khumalo & Yung, 2015; Koot, 2019; Lubilo & Hebinck, 2019; Morton, Winter, & Grote, 2016; Nuulimba & Taylor, 2015; Schnegg & Kiaka, 2018), relative to Zambia, Namibians in the Zambezi region seem to be better off both in terms of monetary and intangible benefits from wildlife. Our results should however be considered of an exploratory nature as we acknowledge that due to multiple testing, there is a risk of false findings.…”
Section: Discussionmentioning
confidence: 99%
“…The disaster risk reduction of crop damage also depends on the ability of the subsistence farmers and stakeholders to deal with hazardous conditions such as poverty, individually and collectively [91,92]. Although farmer compensation schemes against elephant crop damage can significantly socially and economically militate against crop losses and even help attract local support for wildlife conservation [76], they require good planning, implementation and monitoring that overcome the potential myriad of challenges associated with their application at the farm level [14,93].…”
Section: Discussionmentioning
confidence: 99%
“…Community-based conservation is an evolving concept, but for the purpose of this study, we define CBC broadly as an institution that simultaneously enhances human development-especially for people living directly with nature-and conserves biodiversity. Community-based conservation institutions offer incentives to sustainably manage natural resources and have some measure of devolution of resource management responsibilities (Berkes 2007, Plummer and Armitage 2007, Morton et al 2016. Local land users are thought to be ideally central to crafting and implementing conservation and development initiatives in a CBC model (Agrawal 2003, Armitage 2005, Black and Cobbinah 2017.…”
Section: Introductionmentioning
confidence: 99%